2016
DOI: 10.1002/bin.1453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lag Schedules and Response Blocking on Variant Food Consumption by a Girl with Autism

Abstract: Food selectivity by individuals with autism spectrum disorder (ASD) is often viewed in the behavioral literature as a problem with compliance and treated accordingly. However, when viewed as a problem with invariance, it may be appropriate to treat the problem by using procedures that increase variant food consumption. Lag schedules of reinforcement have been shown to increase variability in verbal and play behavior of children with ASD. Therefore, we attempted to evaluate the effects of a lag schedule of posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The results indicated that the Lag 1/DRA procedure resulted in elevated levels of variable responding relative to the DRA procedure for two of the three participants. Subsequent studies further demonstrated the positive effects of lag schedules on other verbal responses (e.g., Esch, Esch, & Love, 2009;Lee & Sturmey, 2014;Susa & Schlinger, 2012), such as tacting (e.g., Heldt & Schlinger, 2012), phonemic variability (Koehler-Platten, Grow, Schulze, & Bertone, 2013), and intraverbals (e.g., Contreras & Betz, 2016), as well as nonverbal responding such as toy play (e.g., Baruni, Rapp, Lipe, & Novotny, 2014) and feeding Silbaugh, Wingate, & Falcomata, 2017).…”
mentioning
confidence: 95%
“…The results indicated that the Lag 1/DRA procedure resulted in elevated levels of variable responding relative to the DRA procedure for two of the three participants. Subsequent studies further demonstrated the positive effects of lag schedules on other verbal responses (e.g., Esch, Esch, & Love, 2009;Lee & Sturmey, 2014;Susa & Schlinger, 2012), such as tacting (e.g., Heldt & Schlinger, 2012), phonemic variability (Koehler-Platten, Grow, Schulze, & Bertone, 2013), and intraverbals (e.g., Contreras & Betz, 2016), as well as nonverbal responding such as toy play (e.g., Baruni, Rapp, Lipe, & Novotny, 2014) and feeding Silbaugh, Wingate, & Falcomata, 2017).…”
mentioning
confidence: 95%
“…Over time, this modification appeared to weaken the response-to-automatic reinforcement relation for both Tumas and Fawn. Silbaugh et al (2017) found similar results in which they applied response blocking to prevent access to invariable behavior (i.e., food consumption). Our outcomes build on their findings and support the utility of blocking and redirection within FCT with lag reinforcement to address repetitive behavior.…”
Section: Discussionmentioning
confidence: 62%
“…Silbaugh and colleagues continued this research with young children with ASD in a series of three studies from 2017 to 2020. Using a Lag 1 schedule, researchers reinforced variability across functionally equivalent vocal mands (Silbaugh et al, 2017(Silbaugh et al, , 2020 or signs (Silbaugh & Falcomata, 2019), rather than across various mand modalities, as in the previous studies. In addition, prompting was used to elicit mands, if necessary, during the intervention condition.…”
mentioning
confidence: 99%
“…Wilcoxon signed rank (Z = − 2.972; p < 0.003) a NSilbaugh and Falcomata (2017), USACase study, reversal designN: 1Age: 4Gender: MDiagnoses: ASDHomeLag schedule of positive reinforcement and NCR30 sessionsA decreasing trend in consumption ( M = 52.5%; range 20–90%) and variety ( M = 2.5; range 2–4) was observed across sessions during lag 0. Lag 1 increased consumption relative to lag 0 but with variability ( M = 53.3%; range 20–90%); variety of foods consumed also increased ( M = 3.06; range 2–4) a NSilbaugh et al (2017), USACase study, baseline and multiple graded interventionsN: 1Age: 3Gender: FDiagnoses: ASDHomeLag schedule of positive reinforcement and Response blocking of invariant consumption, least-to-most prompting and EE36 sessionsNo independent consumption was observed during baseline or Lag1/toys conditions. Lag 1/toys/least-to-most prompting/response blocking increased percentage consumption ( M = 43%).…”
Section: Resultsmentioning
confidence: 98%